Metode Pembelajaran IPS yang Berorientasi pada Peserta Didik: Implementasi Studi di SMP Negeri 1 Jenggawah - Risqy, Lana Iftitahul; Sutomo, Muh.; Salsabilla, Nazlina; Hardini, Sitti (Jurnal Literasi dan Pembelajaran Indonesia, 2025)
This study aims to analyze the implementation of student-oriented learning methods in Social Studies (IPS) at SMP Negeri 1 Jenggawah. The research employed a qualitative case study approach, with data collected through interviews, observations, and document studies. The findings indicate that teachers have implemented various methods such as group discussions, problem-based learning, and the use of technology-based media. The implementation is supported by factors including teacher readiness, facility availability, and student learning motivation. However, the learning process faces obstacles such as limited resources, variations in students' academic abilities, suboptimal time management, and a tendency for teacher dominance in the learning process. This study concludes that the implementation of student-oriented learning is not yet fully optimal. A more profound transformation is required, not only in terms of method variation and facility provision but also in strengthening teachers' pedagogical competence in designing and facilitating learning experiences that are genuinely centered on student needs and active participation.